2006
DOI: 10.1029/2006ja011948
|View full text |Cite
|
Sign up to set email alerts
|

Climatologies of nighttime upper thermospheric winds measured by ground‐based Fabry‐Perot interferometers during geomagnetically quiet conditions: 1. Local time, latitudinal, seasonal, and solar cycle dependence

Abstract: [1] We analyze ground-based Fabry-Perot interferometer observations of upper thermospheric ($250 km) horizontal neutral winds derived from Doppler shifts in the 630.0 nm (red line) nightglow. The winds were measured over the following locations: South Pole (90°S), Halley (76°S, 27°W), Arequipa (17°S, 72°W), Arecibo (18°N, 67°W), Millstone Hill (43°N, 72°W), Søndre Strømfjord (67°N, 51°W), and Thule (77°N, 68°W). We derive climatological quiet time (Kp < 3) wind patterns as a function of local time, solar cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
131
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(148 citation statements)
references
References 50 publications
(77 reference statements)
17
131
0
Order By: Relevance
“…Poleward winds tend to decrease electron density; so if they are more equatorward in solar minimum, it would be expected that the winter anomaly would be more pronounced in solar minimum than in solar maximum. Emmert et al [2006] [Drob et al, 2008], the solar cycle variation of these winds has not yet been included explicitly in a scientific publication. Solar cycle variations in 557.7 nm emissions have been analyzed [Liu and Shepherd, 2007].…”
Section: The Possible Effects Of Transport On Solar Cycle Variations mentioning
confidence: 99%
“…Poleward winds tend to decrease electron density; so if they are more equatorward in solar minimum, it would be expected that the winter anomaly would be more pronounced in solar minimum than in solar maximum. Emmert et al [2006] [Drob et al, 2008], the solar cycle variation of these winds has not yet been included explicitly in a scientific publication. Solar cycle variations in 557.7 nm emissions have been analyzed [Liu and Shepherd, 2007].…”
Section: The Possible Effects Of Transport On Solar Cycle Variations mentioning
confidence: 99%
“…However, there The thermospheric winds over Mount John and Millstone Hill are likely more affected by aurora heating from high latitude (Hagan, 1993) than those over Xinglong. On the other hand, since the Arecibo station is located at low geographical latitude and middle geomagnetic latitude, the thermospheric winds over Arecibo have typical characteristics of middle latitudes (Emmert et al, 2006a).…”
mentioning
confidence: 99%
“…As for the nighttime zonal wind, it was mainly eastward with a peak of ∼ 150 m s −1 . Emmert et al (2006a) have shown that the thermospheric zonal wind over Arecibo exhibited annual variation during solar minimum and exhibited semiannual variation during solar maximum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal amplitudes of the wind decrease with increasing solar activity and vice versa (Igi et al, 1999). Emmert et al (2006) reported that the dependence of the neutral wind on the F10.7 solar flux either weakens or saturates around F10.7=150 at most latitudes and local times. As TEC is an integrated parameter of production, loss and transport processes, the above-mentioned effects may be reflected in the TEC variation.…”
Section: Resultsmentioning
confidence: 99%